Revisiting the Saul narrative in Chronicles : interacting with the Persian imperial context? - Jonker, Louis C. (Old Testament essays, 2010)
It is well-known among biblical scholars and other Bible readers that the Chronicler's presentation of King Saul of Israel differs significantly from the version in 1 Samuel. Many studies have been conducted on this and commentators normally dedicate extensive space to the peculiarity. In line with Knoppers's suggestions of how to approach this peculiarity, this article will investigate whether it could benefit our discussion of the Chronicler's portrayal of King Saul if the perspective of identity formation forms our interpretative key.